Reusing bottom ash as a filler from a Waste-to-Energy plant for making asphalt mastics. (December 2022) - Russo, F.; Veropalumbo, R.; Oreto, C.; Cassese, D.; Papa, B.; Malvezzi, S.
Abstract: Asphalt mastics made up using bottom ash filler (BAF) from Waste-to-Energy plant of A2A Ambiente SpA were investigated, examining both hot and cold mixing processes. Filler-bitumen ratios by weight in proportions of 0.2 and 0.7 were examined: eight mastics were prepared, four of which were made using natural limestone filler (LF) and the remainder using BAF. A leaching test and an X-ray fluorescence (XRF) analysis were performed for each filler. All the asphalt mastics prepared were mainly investigated in terms of their rheological features through an assessment of the shear complex modulus (G*), in addition to the storage modulus (G'), loss modulus (G'') and phase angle (δ). Resistance to permanent deformations under multiple stress creep and recovery loading was investigated measuring non-recoverable creep compliance (Jnr) and percent recovery (%R) at stress levels of 0.1 and 3.2 kPa and temperatures of 40, 50 and 60 °C. Differential scanning calorimetry (DSC) and Thermogravimetric Analysis (TGA) were also carried out in order to ascertain whether the degradation process of the mastics occurred at higher-temperature mixing conditions or operating temperatures. Degradation temperatures were observed above 200 °C due to the presence of the bitumen. Rheological testing showed higher G'/G'' values for cold asphalt mastics made up with BAF for all f/b ratios than for the corresponding solutions made with LF: average increases of 75 % were observed above 10 °C, while they increased by around 99 % above 30 °C, obtaining an 11 % lower phase angle in the latter case. It was also observed that at test temperatures over 40 °C, the mastics made up of BAF showed an overall 90 % decrease of non-recoverable creep compliance compared with the corresponding LF mastics. Leaching tests and the ecotoxicological approach also confirmed the eco-sustainability of all the mastics when subjected to a daphnia EC50 toxicity analysis and an EC50 algal growth test. Highlights: Bottom Ash (BA) can be used as an alternative filler for making performing hot/cold asphalt mastics. The addition of BA does not affect the degradation process of the asphalt mastic above 200 °C. The eco-sustainability of the asphalt mastics was confirmed by the leaching test and ecotoxicological analysis. The greater elasticity of the mastic with BA at high filler content is confirmed when produced cold.